2020
DOI: 10.1155/2020/4793178
|View full text |Cite
|
Sign up to set email alerts
|

Association between Variation of Troponin and Prognosis of Acute Myocardial Infarction before and after Primary Percutaneous Coronary Intervention

Abstract: Background. Circulating levels of cardiac troponin I (cTnI) after ST-segment elevation myocardial infarction (STEMI) were considered as prognostic factors for predicting the incidence of major adverse cardiovascular events (MACE). △cTnI is the difference between peak cTnI after primary percutaneous coronary intervention (PPCI) and cTnI on initial admission. Purpose. This study aimed to assess the relationship between △cTnI, the ratio of △cTnI to cTnI on initial admission, and the incidence of MACE during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…CRP, TNF-α, TGF-β1, IL-6, IL-10, and ESR are deemed early markers of in ammation and tissue damage. Markers of in ammation and cTNI are correlated to myocardial ischemia and injury and are useful for diagnosis and evaluation when treating AMI [3,[22][23][24][25][26][27][28][29]. In ammatory marker and cTnI levels positively correlated with culprit artery thrombosis, no-re ow of the culprit artery, and MACEs [22,25,26], as previous studies have also shown [5,18].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…CRP, TNF-α, TGF-β1, IL-6, IL-10, and ESR are deemed early markers of in ammation and tissue damage. Markers of in ammation and cTNI are correlated to myocardial ischemia and injury and are useful for diagnosis and evaluation when treating AMI [3,[22][23][24][25][26][27][28][29]. In ammatory marker and cTnI levels positively correlated with culprit artery thrombosis, no-re ow of the culprit artery, and MACEs [22,25,26], as previous studies have also shown [5,18].…”
Section: Discussionmentioning
confidence: 82%
“…Markers of in ammation and cTNI are correlated to myocardial ischemia and injury and are useful for diagnosis and evaluation when treating AMI [3,[22][23][24][25][26][27][28][29]. In ammatory marker and cTnI levels positively correlated with culprit artery thrombosis, no-re ow of the culprit artery, and MACEs [22,25,26], as previous studies have also shown [5,18]. We found that cTNI, AST, CRP, and ESR levels were signi cantly lower in STEMI patients given IC tiro ban compared to IV by day 6 post-procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Another protein that regulates the heart muscle contraction and indicates the progression of MI is troponin. 17 Brain natriuretic peptide (BNP) is a cardiac hormone secreted from the cardiomyocytes to maintain normal cardiorenal function. Therefore, serum creatinine, troponin and BNP were evaluated in this research.…”
Section: Methodsmentioning
confidence: 99%
“…However, this study only used creatine kinase-myocardial band (CK-MB) as a marker because cTnI was not collected [19]. More recently, studies on cTnI and post-PCI prognosis have been conducted in patients with acute myocardial infarction (AMI) [20], LM disease [21], chronic total occlusion (CTO) [22], and diabetes mellitus (DM) [23] who are undergoing PCI, but there is a lack of studies involving patients with TVD.…”
Section: Introductionmentioning
confidence: 99%